Technology Design 4.0 to Create Maritime Power - Ananda Meci Hadyanti (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Technological developments and globalization affect the entire system of life. The state as a subject in international life must quickly follow technological developments. State Defense and Security is one of the objects that is always protected. Innovation is a verb that is always required to develop a national defense and security system. Before carrying out innovations, first look at the potential for technology-based security, such as the development of nuclear weapons, biological weapons or information and technology systems that have turned into a non-traditional war potential. Indonesia, one of the countries in the Asian region, needs to anticipate both regional and global opponents to be able to make plans and technological innovations in the future where technology is no longer a noun but a verb that plays a diplomatic role.